Perspektif Ulrich Beck dalam Banjir di Aceh sebagai Risiko Masyarakat Modern - Lili Maimunah; Sisca Indriani; Tiara Resta Lapina; Vieronica Varbi Sununianti; Istiqoma Istiqoma; Deni Aries Kurniawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Flooding in Aceh has become a recurring phenomenon that cannot be understood solely as a natural disaster but also as a result of human activities within modern society. This study aims to analyze flooding in Aceh through the perspective of Ulrich Beck’s risk society theory, focusing on how modernization, environmental change, and development policies contribute to the production of risk. This research uses a literature review approach by examining scientific articles published between 2021 and 2026 from indexed national and international journals. The analysis was conducted thematically to identify patterns, similarities, and research gaps. The findings show that natural factors such as high rainfall and atmospheric conditions act as primary triggers, while human activities including land-use change, river sedimentation, and ineffective policies significantly intensify flood risks. Flooding is therefore categorized as a manufactured risk produced by modern development processes. In addition, the impacts are not limited to ecological damage but also affect social and psychological conditions of society. These results indicate that floods should be understood not only from a technical perspective but also from a social perspective. The study implies that flood management requires a comprehensive approach integrating environmental sustainability, social awareness, and evidence-based policy to reduce both the impact and sources of risk in a sustainable manner.